Facile Electron Transfer in Atomically Coupled Heterointerface for Accelerated Oxygen Evolution (Small 1/2023). Issue 1 (4th January 2023) - Ibrahim, Kassa Belay; Shifa, Tofik Ahmed; Moras, Paolo; Moretti, Elisa; Vomiero, Alberto
Abstract : Accelerated Oxygen Evolution In article number 2204765, Kassa Belay Ibrahim, Alberto Vomiero, and co‐workers design atomically cluster based heterointerface catalyst with strong metal support interaction (SMSI) between WMn2 O4 nanoflakes and TiO2 particles for water splitting. The enhanced oxygen evolution reaction (OER) activity and long term stability of the designed catalyst benefit from the exposed active site and synergetic effect in atomically cluster based heterointerface catalyst.